ETHNOBOTANIC STUDY OF TRADITIONAL MEDICINAL PLANTS IN SEROMBOU INDAH VILLAGE, ROKAN HULU DISTRICT, RIAU PROVINCE - Dahlia; Nofa Nofianti; Ria Karno; Jismi Mubarrak (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The purpose of this study was to determine the plant species used by the community in Serombou Indah village. This research was conducted from March to June 2022. This research is a descriptive research using survey and interview methods. The results showed that 22 families of 27 plant species were used as traditional medicinal ingredients, the most dominant family was the Zingiberaceae family which consisted of 4 species, the Asteraceae family had 2 species and the Piperceae family had 2 species, while the other families had 1 species. The part of the plant that is most widely used as medicine is the leaves of 17 species and the least is the flower and tuber of 1 species. The most common processing method is by boiling 12 species and at least 1 species grated and cut. Diseases that can be treated with a maximum of 9 species of fever and at least 1 species of ringworm, nosebleeds and sprains.